Sisyphus and I - KOSTOVSKI, ILJA (PLAMEN PRESS, 2020)
This collection of rebellious poems are a reflection of Macedonian poet Ilja Kostovski's travels across the United States, as well as his interpretations of God's purpose for man. Written over the course of a decade from the late 1970s, this work arose out of Kostovski's immersion in the 1978 San Francisco poetry scene and his experience of living in the Shaw district of Washington, DC during the 1980s .